DEVELOPMENT OF STRENGTHENING GOOD CHARACTER EDUCATION SCALE AS A NEED ASSESSMENT INSTRUMENT FOR GUIDANCE AND COUNSELING TEACHERS - Awaluddin Tjalla; Wirda Hanim (LPPM Universitas Negeri Jakarta, 2023)
Discussions about morals have been long and have strengthened in Indonesia in the last ten years, marked by character education. Since then, educational institutions have tried to formulate concepts and directions for their implementation. However, there is no scale capable of measuring good character. Therefore, this study aims to develop a scale of good character strengthening Penguatan Karakter Baik (SPKB). This scale consists of three aspects: moral knowing, feeling, and action. Penelitian using research and development (R & D) methods. The respondents of the study were 2468 respondents. The results showed that the moral knowing, feeling, and action instruments were 21 items that met the Validity and, at the same time, the item difference value with a Cronbach's Alpha score of 0.816, so the instrument with 21 items is acceptable as a scale with high reliability.